The identification and the effect of nutrients on the occurrence of harmful algal bloom (HAB) species in Kuantan port, east coast of peninsular Malaysia - Mohammad Noor, Normawaty; Adam, Aimimuliani; Ahmad, Zuhairi (2017)
ABSTRACT Phytoplankton plays an important role in the marine ecosystem. One of the significant contributions of phytoplankton is when the cell proliferate and form Harmful algal blooms (HABs). HABs have been reported in Malaysia more than a decade ago. The occurrence of HAB has increase in terms of number of species and place affected. The events caused negative impact to the aquaculture industry and human health. Therefore, the objectives of this study were to identify phytoplankton species with emphasis to HAB species at Kuantan Port, Pahang and to determine the effect of nutrients on phytoplankton occurrence. Phytoplankton samples collected from Kuantan Port were identified and counted. Nutrients concentrations i.e. nitrate, nitrite, phosphate and ammonia were determined using standard method. From this study several HAB species were identified i.e. Ceratium, Dinophysis spp., Psedonitzschia, Chaetoceros and Prorocentrum micans. A toxic HAB species i.e. Alexandrium tamiyavanichii which was previously reported at the area was not found. Based on statistical analysis, nutrients showed no positive correlation with phytoplankton abundance. This information is important to mitigate HAB in Kuantan, Malaysia.